2013
DOI: 10.1177/1076029613491458
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Extract and Fractions of Fagonia arabica on In Vitro Anticoagulant Activity

Abstract: Fagonia arabica (FA) is a deobstruent and blood purifier, which possesses thrombolytic and antioxidant activities. In this study, the anticoagulant effects of FA and its derived fractions were evaluated. Plasma recalcification was performed with multisolvent extracts of FA and then with extracts prepared successively with increasing polarity of the solvents. Aqueous extract was the most potent anticoagulant extract, which was fractionated by thin-layer chromatography and column chromatography. Five fractions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
(35 reference statements)
1
3
0
Order By: Relevance
“…These results agreed with Ismail et al,14 and Chourasia et al,15 that Fagonia cretica leaves extract and aqueous extract of Fagonia arabica and its fractions exhibited a concentrationdependent anticoagulant activity. A comparison of the effect of the three extracts on the PT and PTT showed that the ethyl acetate and methanol extract exhibited the highest anticoagulant action.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These results agreed with Ismail et al,14 and Chourasia et al,15 that Fagonia cretica leaves extract and aqueous extract of Fagonia arabica and its fractions exhibited a concentrationdependent anticoagulant activity. A comparison of the effect of the three extracts on the PT and PTT showed that the ethyl acetate and methanol extract exhibited the highest anticoagulant action.…”
supporting
confidence: 92%
“…Phytochemical screening revealed that F. schweinfurthii extracts contain alkaloids, cardiac glycolsides, flavonoids, carbohydrates, tannins, saponins, steroids, and amino acids 5 . The anticoagulant activity of Fagonia arabica extracts (water, ethanol, methanol, isopropyl alcohol (IPA), butanol, ethyl acetate, acetone, chloroform, petroleum ether, and hexane) was studied in vitro and revealed that the aqueous extract and its fifth fraction had the greatest anticoagulant effect (31 minutes and 27 minutes, respectively) 15 . Furthermore, Ismail et al, 14 demonstrated that Fagonia cretica had marked anticoagulant activity with a coagulation time of 86.9 seconds.…”
Section: Introductionmentioning
confidence: 99%
“…Mostly used as an astringent, and febrifuge in different regions of the world and use as a prophylactic drug for various diseases like smallpox, liver trouble, stomach ache, dysentery, fever, typhoid, vomiting, piles, skin diseases, toothache and cancer (Rawal et al, 2004;Hussain et al, 2007;Khan Marwat et al, 2008;Akhtar and Begum, 2009;Ali, 2017;Charan et al, 2021). It worked as a blood purifier and a laxative to release constipation (Chourasia et al, 2014). Its extracts from roots and bark are applied for scabies (Baquar, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Heparins (Wu et al, 2012), are a family of highly suiphated acidic mucopolysaccharides that play an important role as anticoagulants in the treatment of thrombotic disease (Fachina and Verli, 2008;Chourasia et al, 2014). However, they also accompanied with some side effects of causing thrombocytopenia and bleeding (Wu et al, 2012;Ekanayake et al, 2008).…”
Section: Introductionmentioning
confidence: 99%